Language Anxiety among EFL Learners: A Review of Causes and Effects - Hydie Claire Gapo; Cryshia Vyneth Antolijao; Renalyn Angob; Joemar Miñoza; M. Saleh Yahya Himni (Asshika: Journal of English Language Teaching and Learning, 2025)
This paper reviews various studies on students' fear of using the English language, commonly known as language anxiety. Many students, especially non-native speakers, experience anxiety when speaking English due to fear of making mistakes, being judged, or lacking confidence. This review analyzed 21 articles published between 2011 and 2024 that investigate students' anxiety in language learning and its effects, organized thematically and in chronological order. All the key influences such as psychological factors, emotional responses, environmental influences, and the cultural factors that affect students’ fear of using the English language will be examined on how they are interconnected with each other. The findings show that language anxiety can seriously harm a student’s academic performance and self-confidence. The review suggests that supportive, friendly, and less judgmental learning environments can help students become more comfortable and confident in using English. It is recommended that further research is needed to develop tailored interventions and include diverse learner populations and every factor that could potentially contribute to the student’s English language anxiety, not only focusing on one factor.